Development of a Root Form Digital Module Based on Canva Site Using a Contextual Approach Containing Numeracy Literacy - Sabrina Fahrunnisa; Soffi Widyanesti Priwantoro (CV. Media Inti Teknologi, 2026)
Background: The focus of this research is to address the minimal use of digital-based interactive media at Muhammadiyah Kasihan Middle School, which has so far been dominated by conventional methods.Aims: This research aims to develop a Canva Site-Based Digital Module with a Contextual Approach Containing Numeracy Literacy on the Root Form material that meets valid and practical criteria.Methods: Product feasibility was evaluated using a validity instrument in the form of a Likert-scale questionnaire addressed to material experts, and a practicality instrument in the form of a student response questionnaire. The validity instrument covered aspects of material, media, language, and design, while the practicality instrument covered ease of use, appearance, and readability of the module. All data obtained were analyzed descriptively quantitatively in the form of percentages to determine the feasibility level of the developed module.Results: The research results show that the digital module is in the very valid category with a percentage of material experts of 80.71% and media experts of 84.76%. The level of practicality of the module based on student responses obtained an average percentage of 80.60% with a very practical category.Conclusion: Based on these results, it can be concluded that the digital module developed is declared technically and substantively feasible as supporting teaching material to help students understand the material on Root Forms through a contextual approach.